A dim view of M-cone onsets - Parry, Neil R. A.; Mckeefry, Declan J.; Kremers, Jan; Murray, Ian J. (Journal of the Optical Society of America A-Optics Image Science and Vision, 2016)
We investigated the brightness (i.e., perceived luminance) of isolated L- and M-cone pulses to seek a perceptual correlate of our previous reports that M-on electroretinograms resemble L-off responses, implying the operation of post-receptoral opponent processing. Using triple silent substitutions, cone increments were generated in a 4-primary ganzfeld, masked by random positive or negative luminance bias. The results show that M-cone increments decrease in brightness, while L-cone increments increase. These differences became smaller as field size reduced; this was not eccentricity or area dependent. We speculate about early retinal input into brightness perception.
EVALuna2:21291